Analisis Kepuasan Pelanggan Terhadap Pelayanan BMT NU Cabang Ajung - Moh Haris Balady; Achmad Roziqin; Ainun Nisa Nurhidayat Hakim; Indra Setiawan (CV. ITTC INDONESIA, 2024)
Baitul Maal wat Tamwil Nahdlatul Ulama (BMT NU) is a microfinance institution operating based on Sharia financial principles. BMT NU offers savings and financing products to help build the economy, particularly at the middle to lower economic levels. BMT NU's products follow Sharia Accounting principles by providing profit-sharing to savings products, thereby boosting the motivation of depositors. Financing at BMT NU Ajung Branch also facilitates transactions using Sharia-compliant contracts and offers popular products like lasisma financing without collateral. This research aims to delve into the role of BMT NU in contributing to community economic empowerment. The research methodology includes analyzing customer satisfaction with BMT NU Ajung Branch services, conducting interviews with BMT NU customers, and reviewing relevant literature. The results indicate that BMT NU not only serves as a provider of Sharia financial services but also plays a role in enhancing financial inclusion, providing sustainable microfinance, and economically empowering the community. The implications of this research can strengthen the understanding of the positive contributions of BMT NU in supporting sustainable economic development at the local level.